Feasibility of cinobufacini for the treatment of oral premalignant lesions: an open-label pilot trial - Yang Liu; Ping Huang; Jie Ming; Yuhong Wang; Yuanyuan Wang; Minghui Wei; Yuan Cui; Jiao Wei; Xinwen Wang (Exploration of Medicine)
Aim: This study aimed to explore the feasibility and preliminary efficacy of cinobufacini in patients with oral premalignant lesions (OPLs). Methods: Patients with histologically confirmed OPLs participated in an open-label uncontrolled pilot clinical study and received a 4-week or 12-week treatment, the efficacy and safety of cinobufacini for the treatment of OPLs were assessed. Results: During the treatment course ranging from 4 weeks to 12 weeks, no one withdrew because of adverse effects, no one had clinical or histologic progressive disease. Of the 8 participants who took cinobufacini for 12 weeks, one had a complete clinical response, and 4 had a complete histologic response. Of note, 9 participants had varying degrees of pain reduction. Conclusions: This small pilot study supports the feasibility of a larger clinical trial to evaluate the efficacy of cinobufacini in the treatment of OPLs [Chinese Clinical Trial Registry (chictr.org.cn) identifier: ChiCTR2300068529].